INNV-32. COMPARING THE MONTREAL COGNITIVE ASSESSMENT (MOCA) FULL AND 5-MINUTE PROTOCOLS IN MILD COGNITIVE IMPAIRMENT SCREENING OF ADULT CNS TUMOR PATIENTS. (14th November 2022) - Kim, Yeonju; Rogers, James; Jammula, Varna; Vera, Elizabeth; Christ, Alexa; Leeper, Heather; Acquaye, Alvina; Boris, Lisa; Briceno, Nicole; Burton, Eric; Choi, Anna; Grajkowska, Ewa; et al.
Abstract: BACKGROUND: Mild cognitive impairment (MCI) commonly occurs in primary CNS tumor patients (PCTP). Our group and others have reported on the Montreal Cognitive Assessment (MoCA) as an MCI screening tool. Several abbreviated MoCA protocols have been developed for telehealth administration in other neurological diseases, with varied literature on scoring and clinical utility. We compared MoCA Full and 5-minute scores to assess utility in neuro-oncology. METHODS: 71 PCTP completed the MoCA Full (abnormal: < 26/30) assessing: visuospatial/executive functioning, naming, memory, attention, language, abstraction, delayed recall, and orientation. Full scores were retrospectively recoded to the Pendlebury MoCA 5-minute protocol (abnormal: < 10/12) assessing: memory, delayed recall, and orientation. Correlation was assessed using Pearson's coefficient. Disagreements between tests were examined using t-test and chi-square test. RESULTS: Patients were primarily White (83%), college-educated (71%) males (54%) diagnosed with glioblastoma (20%), with average age of 43 years (range: 19-75), KPS > 80 (57%), prior radiation treatment (78%), and imaging surveillance at time of testing (79%). MoCA Full and 5-minute mean scores were 25.3 (SD: 4.8) and 9.9 (SD: 2.3), respectively. MCI was indicated in 32% (n= 23) of patients using MoCA Full and 27% (n= 19) using MoCA 5-minute. Where the protocols disagreed, MCI was detected only by MoCA Full in 6 patients (8%), and MoCA 5-minute in 2 patients (3%). Visuospatial/executive (p= 0.025) and abstraction (p< 0.001) subdomain scores, unique to MoCA Full, were significantly associated with MCI detected only by the MoCA Full; other subdomains, patient characteristics, and total score were not significant. The MoCA versions were highly correlated (r= 0.90). CONCLUSION: High correlation and agreement between MoCA Full and 5-minute scores in this neuro-oncology patient population highlight potential telehealth utility of the MoCA 5-minute. Future prospective assessment of the MoCA 5-minute is warranted to describe optimal scoring threshold and utility in neuro-oncology.